Bioconjugates of photon-upconversion nanoparticles for cancer biomarker detection and imaging - Hlaváček, Antonín; Farka, Zdeněk; Mickert, Matthias J; Kostiv, Uliana; Brandmeier, Julian C; Horák, Daniel; Skládal, Petr; Foret, František; Gorris, Hans H (Nature protocols, 2022)
The detection of cancer biomarkers in histological samples and blood is of paramount importance for clinical diagnosis. Current methods are limited in terms of sensitivity, hindering early detection of disease. We have overcome the shortcomings of currently available staining and fluorescence labeling methods by taking an integrative approach to establish photon-upconversion nanoparticles (UCNP) as a powerful platform for cancer detection. These nanoparticles are readily synthesized in different sizes to yield efficient and tunable short-wavelength light emission under near-infrared excitation, which eliminates optical background interference of the specimen. Here we present a protocol for the synthesis of UCNPs by high-temperature co-precipitation or seed-mediated growth by thermal decomposition, surface modification by silica or poly(ethylene glycol) that renders the particles resistant to nonspecific binding, and the conjugation of streptavidin or antibodies for biological detection. To detect blood-based biomarkers, we present an upconversion-linked immunosorbent assay for the analog and digital detection of the cancer marker prostate-specific antigen. When applied to immunocytochemistry analysis, UCNPs enable the detection of the breast cancer marker human epidermal growth factor receptor 2 with a signal-to-background ratio 50-fold higher than conventional fluorescent labels. UCNP synthesis takes 4.5 d, the preparation of the antibody-silica-UCNP conjugate takes 3 d, the streptavidin-poly(ethylene glycol)-UCNP conjugate takes 2-3 weeks, upconversion-linked immunosorbent assay takes 2-4 d and immunocytochemistry takes 8-10 h. The procedures can be performed after standard laboratory training in nanomaterials research.
Keywords: oxid křemičitý; Nanoparticles; Immunosorbents; nádory; Neoplasms; Polyethylene Glycols; polyethylenglykoly; Biomarkers, Tumor; Streptavidin; lidé; Silicon Dioxide; mužské pohlaví; streptavidin; Male; nádorové biomarkery; imunosorbenty; nanočástice; Humans